Peningkatan Kualitas Produk Cokelat Dengan Integrasi Metode Kano Dan QFD - Lukman, Mohammad; Wulandari, Wahyu (Department Industrial Engineering, University of Muhammadiyah Malang, 2018)
The company strives to produce quality products or services. Therefore, companies seek satisfaction or consumer needs so that consumers are satisfied. This study uses the Kano method and QFD. Kano aims to find out the attributes of chocolate products according to consumer desires. Furthermore, QFD gives priority to priority development. The research objective is to find out the product attributes that consumers want and provide information in an effort to improve quality. The results showed that there were 23 attributes which were consumers and 11 who were responsible for making new design designs, checking the composition and quality of raw materials, choosing fonts that were easy to read by consumers, adding filling nuts and eating in promotions via Instagram.